2020
DOI: 10.1161/jaha.119.014120
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Impairs Endothelial Function Through an Exosome‐Mediated Mechanism

Abstract: Background Epidemiological studies have suggested an association between Helicobacter pylori ( H pylori ) infection and atherosclerosis through undefined mechanisms. Endothelial dysfunction is critical to the development of atherosclerosis and related cardiovascular diseases. The present study was designed to test the hypothesis that H pylori infection impaires endothelial function through exosome‐med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 59 publications
4
89
0
Order By: Relevance
“…For the control group, H. pylori infected mice were given the same volume of normal saline. The effectiveness of H. pylori eradication with antimicrobial therapies in mice was confirmed using RUT and Giemsa staining [55,61]. These findings confirm that impairment of endotheliumdependent vasodilation associated with H. pylori infection is reversible in mouse model, similar to the observations in human subjects.…”
Section: H Pylori Infection and Endothelial Dysfunction In Animal Modelssupporting
confidence: 75%
See 2 more Smart Citations
“…For the control group, H. pylori infected mice were given the same volume of normal saline. The effectiveness of H. pylori eradication with antimicrobial therapies in mice was confirmed using RUT and Giemsa staining [55,61]. These findings confirm that impairment of endotheliumdependent vasodilation associated with H. pylori infection is reversible in mouse model, similar to the observations in human subjects.…”
Section: H Pylori Infection and Endothelial Dysfunction In Animal Modelssupporting
confidence: 75%
“…Indeed, Ach-induced endothelium-dependent relaxation was significantly reduced in mice 1 week after H. pylori infection without Helicobacter pylori Infection and Endothelial Dysfunction DOI: http://dx.doi.org/10.5772/intechopen.97260 change in NTG-induced endothelium-independent relaxation. The impaired Achinduced endothelium-dependent relaxation persisted for as long as the infection was present for at least 24 weeks in the infected mice without change in vascular contraction to either phenylephrine or potassium chloride (Figure 1C), while NTGinduced endothelium-independent relaxation remained intact [55]. These data demonstrated that H. pylori infection selectively impairs endothelium-dependent relaxation, not endothelium-independent relaxation, of thoracic aorta in mice that are similar to the findings in human subjects with H. pylori infection.…”
Section: H Pylori Infection and Endothelial Dysfunction In Animal Modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies have shown that certain strains of H pylori might lead CVD by binding von Willebrand factor, interacting with GPIb and inducing platelet aggregation 67 . At the same time, H pylori virulence factors CagA, VacA, heat shock protein (HSP) can also play important roles in the occurrence and development of CVD through their own virulence and the induced immune responses 68 . H pylori CagA‐positive strain infection might be involved in coronary atherosclerosis by changing blood lipids, enhancing LDL oxidation, and activating inflammatory responses 69 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HP -induced exosomal mesenchymal-epithelial transition factor (MET) can exert a pro-tumorigenic effect on tumor-associated macrophages to promote GC progression [ 42 ]. Another study indicated that exosomes from conditioned media of human gastric epithelial cells are involved in the endothelial function impairment in HP infection [ 43 ]. It is also illustrated that exosomal miRNA-155 derived from HP infection macrophages can immunomodulate the inflammatory response to inhibit the gastritis [ 44 ].…”
Section: Role Of Exosomal Rna In the Initiation And Development Ofmentioning
confidence: 99%